Quantitative analysis of Roundup Ready soybean content in soy-derived food and animal feed by using Real-time PCR incorporated with cloned DNA fragments - Khoo, Siew Ping; Cheah, Yoke Kqueen; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Malaysia, Biosafety Bill 2006 was approved by Parliament in July 2007, and labeling legislation will be implemented soon. In this study, duplex polymerase chain reaction (PCR) was carried out to detect endogenous soybean lectin gene and exogenous cp4-epsps (5’-enolpyruvylshikimate-3-phospate synthase) gene simultaneously. Additionally, real-time PCR utilizing SYBR Green fluorescence dye were established for the quantitative analysis of Roundup Ready soybean (RRS), which is based on the two established calibration curve from cloned fragment of cp4-epsps gene and lectin gene respectively. Approximately, 39.5% (45/114) of the samples examined in this study contain RRS, animal feeds (31), processed food (13) and raw soybean (1). Additionally, 75.6% (34/45) of the positive samples were found contained RRS above 0.9%. The sensitive GMO quantitative approach described in this study enable the analysis of various samples and this will facilitate the labeling process.